Stress of students of the Institute of Legal Education Thai Bar Association. - Thawonyutorn, C.; Kalayasiri , R. (Chulalongkorn Medical Journal, 2023)
Background : The stress survey of students at Institute of Legal Education Thai Bar Association in 2008 reported that 58.7 % of students had high to severe stress. Objective : To study stress of the students at the Institute of Legal Education Thai Bar Association. Design : A cross – sectional descriptive study. Setting : Institute of Legal Education Thai Bar Association. Materials and Methods : Four hundred and thirty-five students at the Institute of Legal Education Thai Bar Association were recruited to respond the following: 1) questionnaire on personal information; 2) Suanprung Stress Test–20 (SPST–20); and,3) stress reducing behavior questionnaire. Results : In all, 41.6 % of the subjects had high stress level and 14.3 % severe stress level. Univariate analysis revealed 7 factors significantly associated with stress: health problems, revenue, adequacy of income, savings money, debts, current marital status and negative stress reducing behaviors. The level of stress was predicted by the adequacy of income, health problems and current marital status. Conclusion : We found 41.60 % and 14.3 % of the students had high and severe stress. The stress level is slightly decreased from the survey in 2008. The predictors of high level of stress were adequacy of income, health problems and current marital status.